Coupling of H3K27me3 recognition with transcriptional repression through the BAH-PHD-CPL2 complex in Arabidopsis - Yi-Zhe Zhang (Nature Portfolio, 2020)
Histone 3 Lys 27 trimethylation (H3K27me3) mediates epigenetic silencing of gene expression. Here, Zhang et al. show that in Arabidopsis, the BAH-domain H3K27me3-reader protein AIPP3 forms a complex with PHD proteins and CPL2, a plant-specific Pol II phosphatase, to inhibit Pol II activity by dephosphorylation.